Cardiac tumours in intrauterine life. Issue 10 (October 1992) - Groves, A M; Fagg, N L; Cook, A C; Allan, L D
Abstract : Since 1980, 11 examples of cardiac tumour have been detected in the fetus out of a total of 794 congenital cardiac malformations. Patients were referred because of fetal hydrops in two, a family history of tuberous sclerosis in two, and because of the detection of a tumour mass during a scan at the local hospital in seven. The gestational age range at presentation was from 20-34 weeks. Of eight fetuses where death occurred, the histological type was rhabdomyoma in seven and teratoma in one. In seven cases, the lesion appeared single and in four there were multiple tumours. In two of the cases of rhabdomyoma, other family members had evidence of tuberous sclerosis. Termination of pregnancy took place in four cases; of seven continuing pregnancies, spontaneous intrauterine death occurred in four, and three children are still alive. Two of the three survivors has the clinical picture of tuberous sclerosis. The last case is as yet only 1 month old. In summary, even where the lesion is single, the most likely diagnosis in fetal cardiac tumour is rhabdomyoma, with associated tuberous sclerosis. However, the characteristic features of this latter condition may not become evident until some months after birth.